Peningkatan Kreativitas dan Literasi Keuangan melalui Experiental Learning pada Anggota Dasawisma Seruni 2 - Ainur Rachma Fitriya; Nur Khasanah; Vicky Oktavia; Almira Santi Samasta; Mochammad Eric Suryakencana Wibowo (Pusat Riset dan Inovasi Nasional, 2026)
Abstract. This community service activity aims to improve the creativity, self-development, and financial literacy of Dasawisma Seruni 2 Cempolorejo members through training in making snack bouquets and education on family financial management. The problems faced include low self-confidence, limited creative skills, and suboptimal ability to manage household finances, including determining selling prices and calculating business capital. The activity was carried out using a participatory approach with an experiential learning method that emphasizes learning based on direct experience. A total of 15 participants participated in a series of activities that included self-development materials, basic family financial management, and direct practice in making snack bouquets. Data were collected through observation, discussion, and evaluation of participants' work, then analyzed descriptively qualitatively. The results of the activity showed an increase in participants' creativity and technical skills, understanding of cost planning, and increased motivation to develop home businesses. This activity contributed to strengthening family economic capacity and opening opportunities for sustainable creative skills-based micro-enterprises at the local women's community level of Dasawisma Seruni 2 Cempolorejo.